General practitioners' attitude towards cooperation with other health professionals in managing patients with multimorbidity and polypharmacy: A cross-sectional study. Issue 1 (31st December 2022) - Carrier, Hélène; Zaytseva, Anna; Bocquier, Aurélie; Villani, Patrick; Fortin, Martin; Verger, Pierre
Abstract: Background: Cooperation between general practitioners (GPs) and other healthcare professionals appears to help reduce the risk of polypharmacy-related adverse events in patients with multimorbidity. Objectives: To investigate GPs profiles according to their opinions and attitudes about interprofessional cooperation and to study the association between these profiles and GPs' characteristics. Methods: Between May and July 2016, we conducted a cross-sectional survey of a panel of French GPs about their management of patients with multimorbidity and polypharmacy, focussing on their opinions on the roles of healthcare professionals and interprofessional cooperation. We used agglomerative hierarchical cluster analysis to identify GPs profiles, then multivariable logistic regression models to study their associations with the characteristics of these doctors. Results: 1183 GPs responded to the questionnaire. We identified four profiles of GPs according to their declared attitudes towards cooperation: GPs in the 'very favourable' profile (14%) were willing to cooperate with various health professionals, including the delegation of some prescribing tasks to pharmacists; GPs in the 'moderately favourable' profile (47%) had favourable views on the roles of health professionals, with the exception for this specific delegation of the task; GPs from the 'selectively favourable' profile (27%) tended to work only with doctors; GPs from the 'non-cooperative' profile (12%) did not seem to be interested in cooperation. Some profiles were associated with GPs' ages or participation in continuing medical education. Conclusion: Our study highlights disparities between GPs regarding cooperation with other professionals caring for their patients and suggests ways to improve cooperation.